GE_GERICHTE P/17050/2019 vom 24. April 2023 - GE Cour de justice (2023)
IN DUBIO PRO REO;VOIES DE FAIT;MENACE(DROIT PÉNAL);CONTRAINTE(DROIT PÉNAL);TENTATIVE(DROIT PÉNAL);VIOLATION DU DEVOIR D'ASSISTANCE OU D'ÉDUCATION | CP.126.al1; CP.180.al1; CP.181; CP.219.al1; CP.126.al2.letb; CP.47; CP.49; CP.42.al1; CP.44; CP.51